Memento [videorecording (DVD)] - Nolan, Christopher, 1970-; Pearce, Guy, 1967-; Moss, Carrie-Anne, 1970-; Pantoliano, Joe; Boone, Mark, Jr; Nolan, Jonathan
Leonard Shelby is searching for the man who raped and murdered his wife. He survived, but developed a mind block due to the attack. He can remember everything from before, but memories of anything that followed come and go every few minutes.